Detailing, a key-element in the robustness of concrete composite floors. - ICASP14; Molkens, Tom; François, Stijn; Van Gysel, Ann; Smits, Jules (My University, 2023)
In 2017, a parking building under construction collapsed in Eindhoven, the Netherlands. The reasons were diverse, due to design (including neglect of temperature effect), construction (bundling of bars), product (non-compliant production method) and inspection errors (none of the previous ones noticed or questioned);this despite the fact that the current EN1990 highlights all these facets in its Annex B, reliability differentiation by design supervision, inspection during execution, product properties and inspection levels. Rather coincidentally, just before the collapse, a research campaign was launched at KU Leuven to unravel the joint action in the type of composite flooring used. Such a concrete floor system, according to EN 13747, consists of a prefabricated lower shell and a thicker top layer poured on site, which also contains the overlap reinforcement between the different prefabricated plates. From the test campaign, it became clear that, during the development of any alternative bearing paths, the elementary rules of structural mechanics must be complied with throughout. The overlapping mechanism of reinforcement is only possible as long as the precast slab and the second-phase concrete remain in contact, and for this, the function of the lattice girders is of prime importance. In this sense, it should be regarded that correct detailing rules should be developed for different structural systems to avoid localized failure, affecting a negative impact in the development of alternative load paths. This contribution compares the conclusions of the KU Leuven study with the findings as prepared by the officially appointed committee in the Netherlands. Differences between the two approaches are addressed and conclusions are substantiated with test results. Finally, an analysis is made whether with the rules as proposed in the report of project team WG6T2 "Robustness Rules in Material Related Eurocode Parts" the collapse could have been avoided.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED